2015
DOI: 10.1007/s00438-015-1134-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNAs and genomic DNAs encoding ADP-glucose pyrophosphorylase large and small subunits from sweet potato

Abstract: Interactions between different SSs and LSs were confirmed by a yeast two-hybrid experiment. Our findings provide comprehensive information about AGPase gene sequences, structures, expression profiles, and subunit interactions in sweet potato. The results can serve as a foundation for elucidation of molecular mechanisms of starch synthesis in tuberous roots, and should contribute to future regulation of starch biosynthesis to improve sweet potato starch yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Especially IbAGPb3 , which was scarcely expressed in sweet potato SRs. This result is similar to the findings of a previous study that examined the expression of genes encoding AGPase subunits in sweet potato (Zhou et al, 2016), which showed that IbAGPb3 was only expressed in leaves and IbAGPb2 was expressed in sink tissues at low levels. However, our results also showed that IbAGPb3 was expressed at 95 DAP in the SRs of YS33 and XS22 (Figure 6 and Figure S3D); thus, the tissue specificity and role of this subunit remain to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…Especially IbAGPb3 , which was scarcely expressed in sweet potato SRs. This result is similar to the findings of a previous study that examined the expression of genes encoding AGPase subunits in sweet potato (Zhou et al, 2016), which showed that IbAGPb3 was only expressed in leaves and IbAGPb2 was expressed in sink tissues at low levels. However, our results also showed that IbAGPb3 was expressed at 95 DAP in the SRs of YS33 and XS22 (Figure 6 and Figure S3D); thus, the tissue specificity and role of this subunit remain to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…In sweetpotato, AGPase is a key enzyme controlling starch synthesis and is considered an important determinant of the sink activity of the roots (Yatomi et al 1996;Tsubone et al 2000). Many AGPase genes have been cloned and studied in sweetpotatoes (Lee et al 2000;Seo et al 2015;Zhou et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many key genes have been cloned and functionally characterized in higher plants, especially in the model plant Arabidopsis thaliana and species with starchy organs such as rice, corn, potato, and cassava (Lloyd and Kossmann, 2019;Smith and Zeeman, 2020). Zhou et al (2016) reported the comprehensive cloning of AGPase isoforms in Ipomoea batatas, including two for AGPS and four for AGPL. Similar work has been performed in Nelumbo nucifera (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%